2018
DOI: 10.1051/e3sconf/20184702005
|View full text |Cite
|
Sign up to set email alerts
|

Polyculture of Giant Freshwater Prawn, Macrobrachium rosenbergii and Nilem Carp, Osteochilus hasselti Cultured in Recirculation System Using Biofiltration

Abstract: Giant Freshwater Prawn is one of the freshwater commodity which have an economy value where Nilem carp has also potentially to be cultured to produce fingerling size as a “baby fish”. The purpose of this experiment is to determine the optimal survival, growth, FCR, and productivity of Giant Freshwater Prawn and Nilem carp cultured on polyculture system and also biomass productivity of bio filter (snail, water spinach, and Cabomba). The different stocking density of Nilem carp as a treatments were as followed: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…SGR values in the present study surpass other previous experiments on striped catfish [32,33]. The present findings reveal that the relations between cultivated striped catfish with Nile tilapia in a polyculture system, growth and yield parameters are in close agreement with many reports on other catfish species, as tilapia comes after striped catfish in growth performance [10,[34][35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…SGR values in the present study surpass other previous experiments on striped catfish [32,33]. The present findings reveal that the relations between cultivated striped catfish with Nile tilapia in a polyculture system, growth and yield parameters are in close agreement with many reports on other catfish species, as tilapia comes after striped catfish in growth performance [10,[34][35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“… [ 36 ] The experiment was conducted in a rectangular concrete tank for a duration of 120 days, with the water quality parameters including dissolved oxygen, pH, and temperature being monitored and controlled. [ 42 ] A cylindrical tank made of polyethylene fabric with a thickness of 0.7 mm and a diameter of 6 m, and a depth of 70 cm was used. Factors affecting the growth of freshwater prawns in the prototype pond were controlled by implementing an intelligent water management system.…”
Section: Resultsmentioning
confidence: 99%
“…An optimal temperature for fish life in tropical areas ranges between 25 and 30⁰C. Several studies indicated that Nilem fish can thrive well at temperatures ranging between 18 and 28⁰C [9,27,28].…”
Section: Discussionmentioning
confidence: 99%